1985
DOI: 10.1037/0735-7028.16.3.411
|View full text |Cite
|
Sign up to set email alerts
|

Minors' ability to identify risks and benefits of therapy.

Abstract: The ability to think about risks and benefits of psychotherapy is an important component of the information processing basic to the ability to give informed consent. Minors aged 10 to 20 from a population with learning and behavior problems, with and without prior therapy experience, were asked to list potential risks and benefits ojentering therapy. A relationship was found between age and experience and the tendency to discuss therapy in more abstract ways. However, even young minors and those with no therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 14 publications
2
38
0
Order By: Relevance
“…Sixteen studies examined associations between age and various aspects of competence. Nine studies found no relationship between a child's age and various aspects of competence for consent or assent (Abramovitch et al, 1995;Billick et al, 1998;Casimir & Billick, 1994;Dorn, Susman, & Fletcher, 1995;Fogas et al, 2001;Kaser-Boyd et al, 1986;Mulvey & Peeples, 1996;Susman, Dorn, & Fletcher, 1992), one study found a positive relationship between age and understanding (Billick et al, 2001), and six had mixed results regarding age (Ambuel & Rappaport, 1992;Kaser-Boyd, Adelman, & Taylor, 1985;Scherer, 1991;Tait, Voepel-Lewis, & Malviya, 2003;Urberg & Rosen, 1987;Weithorn & Campbell, 1982). For studies with mixed results, age was associated with some aspects of competence but not with others, or there were age differences for some decision-making scenarios but not for others.…”
Section: For Single-study Results)mentioning
confidence: 96%
See 1 more Smart Citation
“…Sixteen studies examined associations between age and various aspects of competence. Nine studies found no relationship between a child's age and various aspects of competence for consent or assent (Abramovitch et al, 1995;Billick et al, 1998;Casimir & Billick, 1994;Dorn, Susman, & Fletcher, 1995;Fogas et al, 2001;Kaser-Boyd et al, 1986;Mulvey & Peeples, 1996;Susman, Dorn, & Fletcher, 1992), one study found a positive relationship between age and understanding (Billick et al, 2001), and six had mixed results regarding age (Ambuel & Rappaport, 1992;Kaser-Boyd, Adelman, & Taylor, 1985;Scherer, 1991;Tait, Voepel-Lewis, & Malviya, 2003;Urberg & Rosen, 1987;Weithorn & Campbell, 1982). For studies with mixed results, age was associated with some aspects of competence but not with others, or there were age differences for some decision-making scenarios but not for others.…”
Section: For Single-study Results)mentioning
confidence: 96%
“…Another study showed that children with no prior experience in psychotherapy scored higher in terms of reasoning (Kaser-Boyd et al, 1986). Finally, Kaser-Boyd et al (1985) found that children with prior psychotherapy experience were more inclined to say there were no risks of therapy, and inexperienced children were more likely to say that they did not know the benefits of therapy or that a benefit of therapy was to solve problems. The fact that so few studies examined prior experience, as well as the variability regarding the way it was measured (e.g., number of prior hospitalizations versus prior therapy experience), make it difficult to draw conclusions about the influence of prior experience on children's competence.…”
Section: Race and Sesmentioning
confidence: 95%
“…Although information about the development of these skills is limited, as early as third grade students can decide what support they need after assessing their own performance. Students at the elementary and secondary level can often make autonomous decisions regarding scholastic interventions (Deci, Schwartz, Sheinman & Ryan, 1981) and the decisions of adolescents have been shown to be very similar to those of adults (Kaser-Boyd, Adelman & Taylor, 1985). Older adolescents are typically superior to younger adolescents in their strategies to generate options to solve problems and make decisions and their anticipation of the consequences of their decisions (Ormond, Luszcz, Mann & Beswick, 1991).…”
Section: Choice-and Decision-makingmentioning
confidence: 97%
“…Allowing children and young people to make major treatment decisions which can result in significant harm, either immediate or future, or threat to life, is therefore a difficult issue, and competence becomes an important consideration in the debate (Alderson and Montgomery, 1996;Billick et al, 1998Billick et al, , 2001Casimir and Billick, 1994;Degner and Sloan, 1992;de Winter et al, 1999;Kaser-Boyd et al, 1985).…”
Section: Duty Of Care and Protectionmentioning
confidence: 98%